Peningkatan Kesejahteraan Peternak melalui Implementasi Teknologi Pakan dan Pengolahan Limbah Sapi Potong di Kelurahan Rum, Kota Tidore Kepulauan: Improving the Welfare of Livestock Farmers Through the Implementation of Feed Technology and Processing of Beef Cattle Waste in Rum Sub-District, Tidore Islands City - Endrawati, Eny; Hariyono, Dwi Nur Happy; Syafi, Sartika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Cattle are one of the main livestock commodities in North Maluku, as seen in Rum Village, Tidore Islands city. Cattle farming in this area is generally carried out extensively, in a traditional way, with cattle released into pastures or the wild to forage, without permanent pens or supplemental feed. The lack of knowledge and skills of livestock farmers in feed management is a serious problem that leads to low animal productivity. Furthermore, poor management of livestock waste can lead to environmental pollution and the potential spread of disease. Based on these problems, extension and training activities were held on the production of concentrate feed and organic fertilizer to increase livestock productivity and the economic income of livestock farmers in Rum Village, Tidore Islands city. The activities were carried out through several stages: surveys, extension, practice, and monitoring and evaluation, with the active participation of farmers at each stage. The training included producing concentrated feed and compost. Livestock farmers can utilize the resulting concentrated feed and compost. Farmers were able to practice making concentrated feed and compost independently. After the training, farmers' knowledge and skills in implementing good livestock farming practices have improved. Therefore, ongoing mentoring is needed to ensure that farmers can continue to implement appropriate technology to increase livestock productivity.